X-band CMOS Lumped-Component Filter with On-Chip Automated Calibration Using SAR Algorithm - Nedelchev, Marin; Kechev, Jordan (Proceedings (International Conference on Telecommunications and Signal Processing. Online), 2023)
A novel CMOS lumped-component filter with on-chip calibration is proposed on a 45nm silicon on insulator (RFSOI) technology, using inline topology with resonant coupling between resonators. Calibration network is based on successive-approximation register (SAR) algorithm and free running cross-coupled oscillator and also the design freedom given in the synthesis of the filter for choosing the capacitors values [1]. Variation in the 3-dB BW and also transmission zeroes locations is decreased from 1.5GHz to a 100MHz with center frequency of 10 GHz.